Holocaust and its Legacy in the Light of the Contemporary Humanitarian Issues - E. S. Gromoglasova (Vestnik MGIMO-Universiteta)
Abstract: The paper discusses in-depth new perspectives in the Holocaust studies. It pays special attention to the spatiality of the Nazi camps and analyzes the Holocaust geographies more in general. It conceptualizes the camp as a ‘space of lawlessness’ that was created by political means of terror and exclusion. The specific spatiality of the Nazi camp was constructed by perpetrators with intentions to neglect both juridical law and moral laws of humanity. To prove this point the author analyzes P. Levi, the survivor of Auschwitz, witness and his prominent books “The Drowned and the Saved” and “If This Is a Man”. After reading his witness one can conclude that two spatial characteristics of the camp have been the most fundamental. The first one were the borders that cut the camp’s inmates from the people lived in the outside world and made impossible all human relations like providing help, solidarity, empathy. The second one was ‘the grey zone’ - a spatial metaphor that P. Levi used to explain all forms of collaboration with the camp authorities. The presence of the ‘grey zone’ as a main characteristic of the Nazi camp allows us to conceptualize it as a ‘space’ where ‘the starry heavens and internal moral law’ were no more present. So, the Nazi camp is a ‘place of indistinction’, a ‘spatial threshold’ where ‘moral’ and ‘immoral’, ‘human’ and ‘animal’, ‘drowned’ and ‘saved’ were no more distinguishable. The author analyzes more broaden Holocaust geographies outside the camp. Nazis used extensively occupied territories in Eastern Europe to perpetrate their crimes. The author concludes that the geographical localization of the Holocaust was an expression of Nazi irrational genocidal intentions and spatial imaginations. Eastern territories have been constructed by Nazis as ‘broaden spaces of exception and lawlessness’. That spatial imagination and planning allowed the perpetrators to neglect juridical and moral laws in reality. The paper concludes by insisting on the importance of the Holocaust legacy for modern humanitarian action and thinking. The Holocaust legacy helps us to conceptualize more precisely ‘new spaces of lawlessness’. It provides a base for the concepts of human security and ‘global responsibility’ for saving humanity in the contemporary world.